Factors affecting job choice among physician anesthesia providers in Uganda: a survey of income composition, discrete choice experiment, and implications for the decision to work rurally - Tyler J. Law; Shivani Subhedar; Fred Bulamba; Nathan N. O'Hara; Mary T. Nabukenya; Cornelius Sendagire; Adam Hewitt-Smith; Michael S. Lipnick; Janat Tumukunde (BMC, 2021)
Abstract Background One of the biggest barriers to accessing safe surgical and anesthetic care is lack of trained providers. Uganda has one of the largest deficits in anesthesia providers in the world, and though they are increasing in number, they remain concentrated in the capital city. Salary is an oft-cited barrier to rural job choice, yet the size and sources of anesthesia provider incomes are unclear, and so the potential income loss from taking a rural job is unknown. Additionally, while salary augmentation is a common policy proposal to increase rural job uptake, the relative importance of non-monetary job factors in job choice is also unknown. Methods A survey on income sources and magnitude, and a Discrete Choice Experiment examining the relative importance of monetary and non-monetary factors in job choice, was administered to 37 and 47 physician anesthesiologists in Uganda, between May-June 2019. Results No providers worked only at government jobs. Providers earned most of their total income from a non-government job (50% of income, 23% of working hours), but worked more hours at their government job (36% of income, and 44% of working hours). Providers felt the most important job attributes were the quality of the facility and scope of practice they could provide, and the presence of a colleague (33% and 32% overall relative importance). These were more important than salary and living conditions (14% and 12% importance). Conclusions No providers accepted the salary from a government job alone, which was always augmented by other work. However, few providers worked only nongovernment jobs. Non-monetary incentives are powerful influencers of job preference, and may be leveraged as policy options to attract providers. Salary continues to be an important driver of job choice, and jobs with fewer income generating opportunities (e.g. private work in rural areas) are likely to need salary augmentation to attract providers.